VOICE CONTROLLED HUMAN ASSISTENCE ROBOT - chandu, M.Bhanu; Ganapathy, Kirupa (International Journal of Psychosocial Rehabilitation, 2020)
Individual automated colleagues help diminishing the manual endeavours being put by the people in their everyday errands. In this paper, proposed a review on voice-controlled human right hand robot. The human voice directions are given to the human automated colleague remotely, by utilizing a voice order of client. The robot can perform various developments, turns, start/stop activities and migrate an article starting with one spot then onto the next and offering things to the matured individuals in the home. The voice directions are handled, utilizing an advanced mobile phone. The individual human right hand robot is created on a smaller scale controller based stage and can know about its present area. The viability of the voice control conveyed over a separation is estimated through numerous examinations. Execution assessment is completed with consequences of the underlying investigations. Potential enhancements are likewise talked about towards potential applications in home, medical clinics and ventures and compound labs. Key words--Smart assistant robot, control over voice,